2009
DOI: 10.1080/13607860902774402
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delusion of theft in patients with Alzheimer's disease showing mild Dementia in Japan

Abstract: The mechanism underlying delusion in Alzheimer's disease patients has not been fully clarified; however, the occurrence of delusion is a critical issue for dementia patients and their caregivers. In Japan, delusion of theft is the most frequent delusion in AD patients. We examined the risk factors for delusion of theft in AD patients showing mild dementia. Fifty-six AD patients were administered HDS-R, MMSE and COGNISTAT, including the 'speech sample', to assess their neuropsychological and social cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Risk factors such as gender, premorbid personality traits, social cognitive function, and the external environment have been associated with delusions in patients with dementia (Murayama et al, 2009). The examination of the effect of cognitive intervention on delusion was limited in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Risk factors such as gender, premorbid personality traits, social cognitive function, and the external environment have been associated with delusions in patients with dementia (Murayama et al, 2009). The examination of the effect of cognitive intervention on delusion was limited in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the evidence from neuroimaging studies suggesting a distinctive association between episodic memory impairments and DT, few clinical studies have found this association. A previous study identified no significant differences in the scores on Hasegawa’s dementia scale (HDS-R), the MMSE or the Neurobehavioral Cognitive Status Examination (COGNISTAT) sub-scales between the DT (n=14) and ND (n=42) groups [ 14 ]. In addition, another study indicated that delayed recall scores did not correlate significantly with the severity of DT in 22 AD subjects [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 49% of patients with AD and misplacements who had delusions, 36% were delusions of theft. A recent Japanese study assessed the prevalence and risk factors for delusions of theft in a sample of 56 AD patients: 25% of patients had delusions of theft, and these were associated with female gender, absence of cohabiting family members, neurotic personality, and retained social cognitive function [22].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%